(untitled) (Sains Humanika, 2012)
High quality educator will produce high quality human capital. Therefore, the purpose of this study is to determine the level of professionalism education value practices among trainee educator based on Standard Guru Malaysia (SGM). The level of professionalism education value practices is determine based on three elements from 14 original elements in measuring self-domain which is believe in God, leadership and interpersonal and intrapersonal skills. This descriptive research used modified rubric instrument based on SGM and reliability value of the instrument is is 0.87. 188 final year students, who are doing education course at Universiti Teknologi Malaysia, Skudai, Johor have been used as the respondent. Statistical Package for the Social Science (SPSS 16.0) software has been used to analyze raw data of this research. Research findings showed that the overall levels of professionalism value practices by trainee educator are at moderate level (mean 3.31) with leadership elemen at the lowers frequency. Further analysis on believe in God shows that sub-item, which is "integration value believe in God through education process because educator believe it as the highest value in producing good personality" also get the lowers frequency. This interesting finding shows that trainee educator do not have very clear self understanding that integration of self-awareness and believe in God existence as the highest and pre-requisite values for producing good personality character individual. Therefore, this research propose to strengthen professionalism value among trainee educator through training program so that they can understand that the real purpose of education process is to produce good personality character leader based on the highest value which is believe in God.